2017
DOI: 10.5455/ijmsph.2017.0409630062017
|View full text |Cite
|
Sign up to set email alerts
|

A community-based study to assess the treatment adherence and its determinants among hypertensive patients residing in a rural area of Kancheepuram district, Tamil Nadu

Abstract: the health-care delivery system in India. [1,2] Hypertension has been identified as the direct cause of deaths in more than 55% and 25% of all stroke and all coronary heart disease-related deaths reported in India.[3] Even on a global scale, hypertension is one of the most important causes of premature death as per the World Health Organization. [4] Current estimates reveal that hypertension affects more than 30% of adults with age 25 years and above which accounts for almost 1 billion people worldwide.[5] Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…of patients were in the age group of 50-59. The findings were similar with the data reported by Sunita Parma et al 4 Prevalence of non-adherence among hypertensive patient was found to be 54% in a study conducted by Arjun Balasubramanian et al 19 Similarly a study conducted at a healthcare facility in north India by Siraj Ahmad et al 20 showed prevalence of non-adherence among hypertensive patient to be 42.8%. Study conducted by Prateek et al 21 have reported non-adherence to be 87% among hypertensive patients in rural area of Tamil Nadu.…”
Section: Discussionsupporting
confidence: 86%
“…of patients were in the age group of 50-59. The findings were similar with the data reported by Sunita Parma et al 4 Prevalence of non-adherence among hypertensive patient was found to be 54% in a study conducted by Arjun Balasubramanian et al 19 Similarly a study conducted at a healthcare facility in north India by Siraj Ahmad et al 20 showed prevalence of non-adherence among hypertensive patient to be 42.8%. Study conducted by Prateek et al 21 have reported non-adherence to be 87% among hypertensive patients in rural area of Tamil Nadu.…”
Section: Discussionsupporting
confidence: 86%
“…Prescription of ≥ 4-5 pills/day has been significantly associated with non-adherence in CKD patients. 13,24,25 Although difficult, few measures to minimise non-adherence could be to prescribe cheaper generic medicines, reduce the amount and frequency of drugs, prescribing the drug combinations for hypertension, DM and anemia, giving priority to long-acting formulations, use of long-acting insulin when indicated, judicious use of antibiotics, multivitamins and PPIs/H2 blockers.…”
Section: Discussionmentioning
confidence: 99%
“…The final score described the adherence levels; a perfect eight meant high adherence, a score from seven to six meant medium adherence and, finally, a score less than six meant low adherence. 17 Furthermore, only patients with high adherence scores were considered adherent and those with low and medium adherence scores were considered non-adherent. Anthropometric measurements of weight and height were taken.…”
Section: Introductionmentioning
confidence: 99%